2005
DOI: 10.1007/s00401-005-0990-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of mitochondria in myasthenia gravis complicated with dermatomyositis and rheumatoid arthritis: a case report

Abstract: We report a 57-year-old male with myasthenia gravis complicated with dermatomyositis and rheumatoid arthritis without evidence of thymoma. He showed prominent muscle wasting and weakness in the four extremities and trunk in addition to swallowing disturbance. He showed intolerance to exercise on a bicycle ergometer, and muscle biopsy specimens demonstrated ragged-red fibers. An anti-acetylcholine receptor (AChR) antibody was detected in his serum but no anti-mitochondrial M2 component antibody was found. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Indeed, we found that the clinical features in patients with AMAs showed great variability. Firstly, although AMAs only occurred in adult IIM patients, the age at onset ranged from 23 years to 86 years and the mean age at onset ranged from the fourth decade to the seventh decade [3][4][5]7,8,[20][21][22][23][24][25][26] . Besides, the average disease duration varied from 10 months (in our study) to 6.5 years, and the prevalence of chronic disease duration varied from approximately 30% (in our study) to 85% [3,5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the clinical features in patients with AMAs showed great variability. Firstly, although AMAs only occurred in adult IIM patients, the age at onset ranged from 23 years to 86 years and the mean age at onset ranged from the fourth decade to the seventh decade [3][4][5]7,8,[20][21][22][23][24][25][26] . Besides, the average disease duration varied from 10 months (in our study) to 6.5 years, and the prevalence of chronic disease duration varied from approximately 30% (in our study) to 85% [3,5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…The muscle tissue of patients with MG display abnormal mitochondrial morphology and function, and the energy levels are often significantly lower than normal ( 44 , 45 ). Similarly, abnormally shaped and structured mitochondria on muscle biopsy, ragged-red fibers, loss of mitochondrial respiratory chain complexes-1 and muscle aerobic dysfunction were observed in MG ( 46 , 47 ). These previous findings suggest the presence of mitochondrial abnormalities in neuromuscular diseases, such as MG, which may lead to muscular weakness.…”
Section: Mitochondrial Dysfunction Disordersmentioning
confidence: 80%
“…MG and IMs are both acquired diseases caused by autoimmune responses against neuromuscular junctions and muscle tissues, respectively. Although both 2 diseases are rare, there have been cases of MG and IM co-occurrence, and it is increasingly being recognized that the comorbidity of MG and IMs could be related to thymoma as a paraneoplastic phenomenon (62)(63)(64)(65)(66)(67)(68).…”
Section: Inflammatory Myopathymentioning
confidence: 99%